Spectroscopic Analysis of Clove Plasma Parameters Using Optical Emission Spectroscopy - Majeed, Neean F.; Naeemah, Maysaa R.; Ali, Alyaa H.; Mazhir, Sabah N. (Iraqi Journal of Science, 2021)
In the current study, the emission spectra generated from clove were measured under normal atmospheric pressure with different laser energies. Clove is used as a source of essential oil in herbal medicine, in particular as a dynamic analgesic oil in dental and other diseases. For aromatherapy, Antiseptic, antiviral, and antimicrobial agents are also packaged with cloves. Compounds that reduce inflammation tend to battle sore throats, cold, and cough as they display so many advantages. The measured spectrum reveals distinctive lines of clove’s chemical elements. X-ray fluorescent (XRF) and atomic absorption spectrometry (AAS) were used to measure the spectrum generated or absorbed by detecting the presence of various elements and their ratios in the cloves, for different energy the electron temperature varies between 0.043 and 0.073 eV and the number of electron varied between 2.074 and 2.287) x1014 cm-3 for clove.